ANALYSIS ON THE CHARACTERISTICS OF EX-MINING SOIL AFTER 5 YEARS AND 10 YEARS OF REVEGETATION - Hermansyah Hermansyah; Yuningsih Lulu; Ibrahim Eddy; Marsi Marsi (Media Konservasi, 2021)
Open-pit mining has affected landscapes and ecosystem balances immensely. The effects are including altered soil surface, decreased soil productivity, soil compaction, erosion and sedimentation, declined biodiversity, as well as deteriorated hydrological, hydrogeological, and atmospheric function of the surrounding area. Reclamation is one of the environmental restoration efforts that could be taken to improve these conditions. Physical and chemical properties of soil are the indicators of soil damage level as well as the success indicator of the reclamation program. This study aims to analyze the changes in post-mining soil characteristics after 5 years and 10 years of revegetation. The sample was selected by the purposive sampling method based on the age of plants and the vegetation density. The physical properties of post-coal soil after 5 years of revegetation are characterized by high soil acidity, low in organic matter (OM)/soil organic carbon (SOC), very low total N (nitrogen), moderate P availability, extremely high K2O, and moderate CEC. Whilst, the post-coal mining soil after 10 years of revegetation is found to be acidic (low pH), with moderate SOC, low total N, low P, very high K2O, and moderate CEC. Heavy metal (Fe, Mn, Al) contents in ex-coal mining reclamation area after 5 years and 10 years revegetation found to be in the high category. Key words: post-mining land, revegetation, soil characteristics